Development of Interactive Learning Media Using Genially to Improve Cognitive Ability in Batik Design Learning - Agita Ainur Rizqiyah; Sri Endah Wahyuningsih; Samsudin Anis (Jurnal Penelitian Pendidikan, 2026)
Learning batik motif design at Vocational High Schools requires learning media that can facilitate conceptual understanding visually and interactively in accordance with students’ characteristics. However, the use of interactive learning media that supports the​ improvement of students’cognitive abilities at SMKN 3 Pekalongan is still limited. This study aims to develop interactive learning media using Genially and to analyze its effectiveness in improving students’ cognitive abilities in traditional and contemporary batik elements at SMKN 3 Pekalongan. This study employed a Research and Development (R&D) method using the ADDIE model. The research subjects consisted of 61 eleventh-grade KKBT students, who were divided into an experimental class and a control class to examine the effectiveness of the developed learning media. The efectiveness test showed an increase in the learning outcomes in the experimental class from 74.45 to 89.55, with N-gain value 0.657 (moderate category), while the control class obtained an N-gain of 0.21 (low category). The Independent Sample Test results indicated a significant difference in learning outcomes between the experimental class and the control class. Therefore, the Genially-based interactive learning media is declared feasible, practical, and effective for use in learning.